Safety of catheter‐directed thrombolysis for massive and submassive pulmonary embolism: Results of a multicenter registry and meta‐analysis. Issue 4 (1st February 2017) - Bloomer, Tyler L.; El‐Hayek, Georges E.; McDaniel, Michael C.; Sandvall, Breck C.; Liberman, Henry A.; Devireddy, Chandan M.; Kumar, Gautam; Fong, Pete P.; Jaber, Wissam A.
Abstract : Objectives: To evaluate the safety and efficacy of catheter‐directed thrombolysis (CDT) in the treatment of acute pulmonary embolism (PE). Background: The use of CDT for the treatment of acute submassive and massive PE is increasing in frequency. However, its safety and efficacy have not been well elucidated. Methods: This study is made of two parts: one is a two‐center registry of acute PE patients treated with CDT. The safety outcome evaluated was any major complication including fatal, intracranial (ICH), intraocular, or retroperitoneal hemorrhage or any overt bleeding requiring transfusion or surgical repair. The efficacy outcome was acute change in invasive pulmonary artery systolic pressure (PASP). The second part is a meta‐analysis of all contemporary studies that used CDT for PE. Reported outcomes are the same as in the registry, with the addition of right ventricular to left ventricular (RV/LV) ratio change. Results: In the registry, 137 patients were included (age 59 ± 15, 50% male, 88% submassive PE). ICH occurred in two patients and major complications in 13 (9.4%). PASP decreased post procedure by 19 ± 15 mm Hg (95% CI 16–23). In the meta‐analysis, 16 studies were included with 860 patients. Rate of ICH was 0.35% and the major complication rate was 4.65%, most requiring transfusion only. In‐hospital mortality was 12.9% in the massive and 0.74% in the submassive group. All studies showed improvement in PASP and/or RV/LV ratio post CDT. Conclusions: CDT is associated with a low major complication rate. Randomized studies are needed to evaluate its efficacy relative to anticoagulation alone. © 2017 Wiley Periodicals, Inc.